Cytoprotective effect of palm kernel cake phenolics against aflatoxin B1-induced cell damage and its underlying mechanism of action - Oskoueian, Ehsan; Abdullah, Norhani; Idrus, Zulkifli; Ebrahimi, Mahdi; Karimi, Ehsan; Goh, Yong Meng; Oskoueian, Armin; Shakeri, Majid (BioMed Central, 2015)
Background: Palm kernel cake (PKC), a by-product of the palm oil industry is abundantly available in many tropical and subtropical countries. The product is known to contain high levels of phenolic compounds that may impede the deleterious effects of fungal mycotoxins. This study focused on the evaluation of PKC phenolics as a potential cytoprotective agent towards aflatoxin B1 (AFB1)-induced cell damage. Methods: The phenolic compounds of PKC were obtained by solvent extraction and the product rich in phenolic compounds was labeled as phenolic-enriched fraction (PEF). This fraction was evaluated for its phenolic compounds composition. The antioxidant activity of PEF was determined by using 1,1-diphenyl-2-picryl-hydrazil scavenging activity, ferric reducing antioxidant power, inhibition of ß-carotene bleaching, and thiobarbituric acid reactive substances assays. The cytotoxicity assay and molecular biomarkers analyses were performed to evaluate the cytoprotective effects of PEF towards aflatoxin B1 (AFB1)-induced cell damage. Results: The results showed that PEF contained gallic acid, pyrogallol, vanillic acid, caffeic acid, syringic acid, epicatechin, catechin and ferulic acid. The PEF exhibited free radical scavenging activity, ferric reducing antioxidant power, ß-carotene bleaching inhibition and thiobarbituric acid reactive substances inhibition. The PEF demonstrated cytoprotective effects in AFB1-treated chicken hepatocytes by reducing the cellular lipid peroxidation and enhancing antioxidant enzymes production. The viability of AFB1-treated hepatocytes was improved by PEF through up-regulation of oxidative stress tolerance genes and down-regulation of pro-inflammatory and apoptosis associated genes. Conclusions: The present findings supported the proposition that the phenolic compounds present in PKC could be a potential cytoprotective agent towards AFB1 cytotoxicity.